Burger's Medicinal Chemistry and Drug Discovery 2003
DOI: 10.1002/0471266949.bmc057
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Hypoglycemic Agents

Abstract: This chapter focuses on insulin and hypoglycemic agents. It surveys the drugs available for treatment of hyperglycemia associated with diabetes mellitus: insulin and its analogs, insulinotropic agents, insulin‐sensitizing agents, and α‐glucosidase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 193 publications
0
2
0
Order By: Relevance
“…The pKa value for thiazolidine-2,4-dione (1) heterocyclic ring is about 6.8 and thus this class of compounds is partially ionized at physiological PH is depicted in Figure 2. ▪ Removal of acidic head function of thiazolidine-2,4-dione (1) heterocyclic ring by N-methylation taken place at 3-position, which lead to loss of oral hypoglycemic activity 80,81 . However, methylation of the imide nitrogen of thiazolidine-2,4-dione (1) heterocyclic ring, which shows good oral hypoglycemic activity only at high level of dose of glitazones.…”
Section: Structure-activity-relationship (Sar) Studies Of Thiazolidinmentioning
confidence: 99%
See 1 more Smart Citation
“…The pKa value for thiazolidine-2,4-dione (1) heterocyclic ring is about 6.8 and thus this class of compounds is partially ionized at physiological PH is depicted in Figure 2. ▪ Removal of acidic head function of thiazolidine-2,4-dione (1) heterocyclic ring by N-methylation taken place at 3-position, which lead to loss of oral hypoglycemic activity 80,81 . However, methylation of the imide nitrogen of thiazolidine-2,4-dione (1) heterocyclic ring, which shows good oral hypoglycemic activity only at high level of dose of glitazones.…”
Section: Structure-activity-relationship (Sar) Studies Of Thiazolidinmentioning
confidence: 99%
“…▪ Replacement of central phenoxyalkyl linker (B) by naphthalene ring to give netoglitazone (14) compound of thiazolidine-2,4-diones class, which show more potent activity, as compared to rosiglitazone (4) 44 . Liphophilic Tail ▪ The brief review of oral hypoglycemic activity of thiazolidine-2,4-diones were shown that, incorporation of wide varieties of mostly aromatic and heteroaromatic rings present at liphophilic tail region were produced active agents of thiazolidine-2,4-diones class 80 . ▪ The lipophilic tail is attached to N-CH3 group of phenoxyethyl moiety of phenoxyalkyl linker (B).…”
mentioning
confidence: 99%